Vemurafenib Synergizes with Nutlin-3 to Deplete Survivin and Suppress Melanoma Viability and Tumor Growth - Ji, Zhenyu (2013)
BACKGROUND: For patients with advanced melanoma, primary and secondary resistance to selective BRAF inhibition remains one of the most critically compelling challenges. One rationale argues that novel biologically-informed strategies are needed to maximally cripple melanoma cells up front before compensatory mechanisms emerge. Since p53 is uncommonly mutated in melanoma, restoration of its function represents an attractive adjunct to selective BRAF inhibition. EXPERIMENTAL DESIGN: Thirty-seven BRAF(V600E)-mutated melanoma lines were subjected to synergy studies in vitro using a combination of vemurafenib and nutlin-3 (Nt-3). In addition, cellular responses and in vivo efficacy were also determined. We also analyzed changes in the levels of canonical apoptotic/survival factors in response to vemurafenib. RESULTS: Dual targeting of BRAF(V600E) and HDM2 with vemurafenib and Nt-3, respectively, synergistically induced apoptosis and suppressed melanoma viability in vitro and tumor growth in vivo. Suppression of p53 in melanoma cells abrogated Nt-3′s effects fully and vemurafenib’s effects partially. A survey of canonical survival factors revealed that both vemurafenib and Nt-3 independently attenuated levels of the anti-apoptotic protein, survivin. Genetic depletion of survivin reproduces the cytotoxic effects of the combination strategy. CONCLUSION: These results demonstrate preclinical feasibility for overcoming primary vemurafenib resistance by restoring p53 function. Moreover, it identifies survivin as one downstream mediator of the observed synergism and a potential secondary target.